APPLICATION OF DECORATED PANDAN LEAVES AND AROMATHERAPY TO REDUCE BLOOD PRESSURE IN ELDERLY PARENTS WITH HYPERTENSION: CASE REPORT - Koernia Nanda Pratama; Luqman Hakim; Arif Setyo Upoyo (International Journal of Biomedical Nursing Review, 2024)
Introduction: Hypertension is one of the health problems that requires constant attention. This is because it can affect more serious health conditions for sufferers. The complications that can arise in hypertension cases include heart attack, stroke, aneurysm, kidney failure, eye problems, and can cause death. The actions taken to overcome this risk is by applying non-pharmacological therapy, such as boiled pandan leaves. Purpose: This case study aims to provide an overview of the application of boiled pandan leaves to health problems in hypertention cases in Banteran Village, Sumbang Subdistrict. Methods: This case study was carried out using the case-study analysis method based on nursing intervention. The case study was conducted in November 2023 with research subjects who were sufferers of hypertension. Discussion: The results of this case study show that after being given nursing intervention with non-pharmacological therapy boiled and aromatherapy pandan leaves once a day for 7 days, blood pressure decreased. Conclusion: Application of boiled pandan leaves can reduce blood pressure levels in hypertension health problems.